BANTUAN LUAR NEGERI JEPANG DALAM SKPT MOROTAI, MALUKU UTARA - Irmawati, Irmawati; Watania, Patricia Benedicta (Journal of Urban Sociology, 2021)
Japan provided bilateral assistance for the construction of SKPT Morotai in North Maluku Province with an aid value of Rp 1.8 billion in 2018. Foreign assistance or Official Development Assistance is used for physical development and capacity building in the fisheries sector. Thus, the fisheries sector could enter export markets including to Japan. In the study of political economy, the economic policy of the country is not only related to purely economic affairs but is influenced by political interests. The state will use its power to maximize the national interest. Based on the results of the study, it was found that Japan as a donor country uses ODA as a foreign policy instrument based on economic interests and political interests in Indonesia. Economically, Japan benefits from the presence of fish products from Morotai, but on the other hand Japan does not want the dominance of fish products from Indonesia by imposing import duties. Politically, ODA becomes a means of concession of trade protection policies in the fisheries sector even though Indonesia and Japan have signed free trade agreements.Â Keywords: Jepan, SKPT Morotai, North Maluku